Cultural Tourism Development Strategy of Penyengat Island Tanjungpinang City - Primantoro Nur Vitrianto; Muhammad Patiyusuf (Jurnal Mantik, 2022)
The role of the Tanjungpinang City Culture and Tourism Office in carrying out regional regulations must be in accordance with the objectives desired by the local government. The regulations that appear to regulate this show that these regulations do not appear to be supported by the readiness of government officials in their implementation from above and below and the lack of public awareness about the existence of these policies. For this reason, the Tanjungpinang City Culture and Tourism Office is tasked with implementing regulations, one of which is managing the development of Penyengat Island which is comfortable for tourists to visit and also to create government administration and community activities in Tanjungpinang City. The strategy carried out is expected to be able to answer the various challenges of the Department of Culture and Tourism that have not been maximized regarding planning and implementation. This study uses a qualitative approach using in-depth interviews and is supported by observations and documents. In this research, scenario planning is used to answer the results of what the researcher wants to get. The supporting and inhibiting factors that are built from the management of cultural tourism are both a strength and a weakness in managing cultural tourism, of course the right strategic steps will be taken by policy makers to get a solution that has a good impact on cultural tourism on the island of Penyengat. In its implementation there are supporting factors, namely the level of education, regulations and budget sources and inhibiting factors which are external factors in this case the local community who are less concerned and less contributing to developing cultural tourism. Currently, Penyengat Island is included in scenario 3 category, namely the cultural tourism of Penyengat Island with low selling value.